2012
DOI: 10.1002/ar.22428
|View full text |Cite
|
Sign up to set email alerts
|

Hadrosaurs Were Perennial Polar Residents

Abstract: Recent biomechanical evidence has fuelled debate surrounding the winter habits of the hadrosaurian dinosaur Edmontosaurus (ca. 70 Ma). Using histological characteristics recorded in bone, we show that polar Edmontosaurus endured the long winter night. In contrast, the bone microstructure of temperate Edmontosaurus is inconsistent with a perennially harsh environment. Differences in the bone microstructure of polar and temperate Edmontosaurus consequently dispute the hypothesis that polar populations were migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
9
46
0
Order By: Relevance
“…Beside LAGs and annuli, we observed vascularization shifts in the primary bone of two Kentrosaurus samples. These are very similar to the textural shifts documented in the polar Edmontosaurus (Chinsamy et al, ), in which periodic shifts from circumferential to reticular FLB are observed. Shifts are less distinct in Kentrosaurus than in the polar Edmontosaurus , but they are more distinct and frequent than in the temperate Edmontosaurus (Chinsamy et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Beside LAGs and annuli, we observed vascularization shifts in the primary bone of two Kentrosaurus samples. These are very similar to the textural shifts documented in the polar Edmontosaurus (Chinsamy et al, ), in which periodic shifts from circumferential to reticular FLB are observed. Shifts are less distinct in Kentrosaurus than in the polar Edmontosaurus , but they are more distinct and frequent than in the temperate Edmontosaurus (Chinsamy et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Bone histology of extinct animals provides a host of information about their biology (e.g., Erickson and Brochu, ; Botha and Chinsamy, ; Botha‐Brink and Smith, ; Hugi et al, ; Chinsamy‐Turan, ; Prondvai et al, ), and such studies have been widely applied to the Dinosauria (e.g., de Ricqlès, ; Reid, ; Erickson and Tumanova, ; Horner et al, ; Tütken et al, ; Erickson, , Chinsamy‐Turan, ; Cerda and Chinsamy, ; Chinsamy et al, ). However, there is a distinct scarcity of studies of stegosaur bone histology, which may be directly related to the rare occurrence of stegosaurs in the fossil record (Maidment, ).…”
mentioning
confidence: 99%
“…This locality represents the most northerly occurrence of ankylosaur skeletal remains during the Cenomanian, and further solidifies this group, and dinosaurs in general, as persistent residents of high latitude regions [39]–[41]. The region experienced large fluctuations in solar radiation through the year due to its high latitude, likely leading to seasonal growth patterns in vegetation, however these dinosaurs likely persisted in the area as they would have been physically unable to migrate long distances [15],[41]–[42].…”
Section: Discussionsupporting
confidence: 68%
“…4). A similar repeating zonal vascular pattern is described in other dinosaurs (Horner et al 1999;Hübner 2012;Hedrick et al 2014) including the hadrosaurid Edmontosaurus (Chinsamy et al 2012). Alaskan specimens of Edmontosaurus were hypothesized to exhibit this vascular cyclicity in place of LAGs and in response to annually reduced nutrient access resulting from non migratory behavior and months of polar darkness (Chinsamy et al 2012).…”
Section: Discussionmentioning
confidence: 71%